Peran Artificial intelligence (AI) dalam Personalisasi Proses Pembelajaran Mahasiswa di Pendidikan Tinggi - Fatmawati Fatmawati; Mike Nurmalia Sari; Yanti Setianti; Khairul Saleh; Dedek Helida Pitra (Journal on Education, 2024)
This research aims to investigate the impact of artificial intelligence (AI) technology usage in enhancing learning effectiveness at the higher education level. The research methodology involves analyzing relevant literature and conducting interviews with students and educators who have utilized AI technology in the learning context. The findings indicate that the integration of AI technology can provide a more personalized, adaptive, and focused learning experience, consequently enhancing student engagement and academic performance. However, challenges related to data privacy and technical readiness also need to be addressed to ensure the successful implementation of AI technology in higher education.